The hidden burden of cervical and low back pain among women in conflict-affected Yemen - Muafa, Hussein Mussa; Balkam, Malika Abdu (Frontiers in Musculoskeletal Disorders, 2025)
BackgroundMusculoskeletal disorders, particularly cervical and low back pain (CLBP), are leading causes of disability worldwide. However, evidence from conflict-affected and low-resource regions such as Yemen remains scarce. This study aimed to determine the prevalence, associated risk factors, and radiological patterns of CLBP among women attending a tertiary hospital in Sana'a, Yemen.MethodsA hospital-based cross-sectional study was conducted among 470 adult female patients at Al-Gumhori Teaching Hospital, Sana'a, from January to March 2025. Participants completed structured questionnaires covering sociodemographic characteristics, lifestyle behaviors, psychological stress, and musculoskeletal symptoms. CLBP was defined according to European Guidelines as non-traumatic spinal pain persisting ≥12 weeks. Radiological assessments (x-ray and MRI) were performed in clinically indicated cases. Multivariable logistic regression identified independent factors associated with CLBP.ResultsThe prevalence of cervical and/or low back pain was 69.4% (95% CI: 65.2–73.3). Independent factors associated with CLBP included obesity (aOR = 2.56; 95% CI: 1.54–4.25), physical inactivity (aOR = 1.91; 95% CI: 1.13–3.24), prolonged screen time >4 h/day (aOR = 1.73; 95% CI: 1.01–2.98), and moderate-to-severe anxiety symptoms (aOR = 3.12; 95% CI: 1.79–5.45). Radiological findings revealed cervical muscle spasm in 62%, vertebral osteophytosis in 33%, and lumbar disc prolapse in 28%.ConclusionCLBP is highly prevalent among Yemeni women, with multiple modifiable risk factors linked to lifestyle and psychological distress. Targeted, integrated public health strategies are urgently needed to reduce musculoskeletal disability among women in conflict-affected regions.